66.9k views
4 votes
Help pls. Show your work!!

Help pls. Show your work!!-example-1

1 Answer

7 votes

Answer:

True

Explanation:

given
f(x)=\sqrt[4]{2x-6} and
g(x)=(1)/(2) x^(4)+3

to find the inverse we just switch the x and y values for one of the functions,

in this case I will chose f(x) [note f(x) is just another way of saying y]


x=\sqrt[4]{2y-6}

solve for x;

raise both sides to the 4th power


x^(4)=2y-6

add 6 to both sides


x^(4) +6=2y-6-6\\=x^(4)+6=2y

divide both sides by 2 and you get


(x^(4) +6)/(2) =(2)/(2) y

simplify and you get


y=(1)/(2) x^(4) +3

which equals to g(x).

hope this helps, for practice, I would recommend you switch the x and y of g(x)

User Geon George
by
5.4k points